A National Study of Adult Women Sexually Abused by Clergy: Insights for Social Workers. Issue 2 (25th January 2022) - Pooler, David Kenneth; Barros-Lane, Liza
Abstract: Given the paucity of research on the experiences of women who are sexually abused by clergy as adults and the advent of the #ChurchToo movement in 2017, the results of a mixed-methods national study highlight the experiences of those who survived the abuse and report on what factors are most healing in their recovery. Internet-based surveys with both quantitative and qualitative items were completed by 159 respondents. Less than 10 percent reported receiving help and support from their congregation after they reported the abuse, and about half of the respondents were blamed for the abuse and ignored by people in their congregations. In spite of the poor responses from their churches, these respondents reported positive beliefs regarding their ability to recover and heal. Mental health counseling was listed as a primary mechanism for healing. Multiple regression was used to develop a model of resilience. Faith in God was the most salient predictor. Those who survived sexual abuse need social workers who can navigate the complex set of factors and issues at the intersection of religion/spirituality, mental health treatment, and policy advocacy, including the ability to see what has been helpful about religious experiences and what has not.